Power unto Sickness, Sickness unto Power in the Periphery of Soviet Psychiatry - Tomas Vaiseta (Acta Medico-Historica Rigensia)
The three most important processes in psychiatric hospitals of the Lithuanian SSR (1944–1990) have been analysed in terms of the centre-periphery relation. Two of them are named “power unto sickness”, that is, the Soviet state’s efforts to influence people with deviant behaviours who were considered to have “mental diseases”. The first process could be considered external: institutionalisation of psychiatric system in the Lithuanian SSR that was meant to create the conditions, forms and means to exercise the said influence. The main outcome of the process is said to be the so-called “institution addiction” where problems arising from institutionalisation are tackled with more institutionalisation. The second process in the “power unto sickness” category is internal. The Soviet psychiatric model used in the Lithuanian SSR has been analysed and the question whether there has ever been a homogenous and unique model of Soviet psychiatry has been raised. The third process is the symbolic inverse of the “power unto sickness” processes, but determined by them – “sickness unto power”. It shows the “power” itself to be deviant, transgressing formal limits, exposes the consequences and cracks of its exercise. The third process in psychiatric hospitals of the Lithuanian SSR, “parallelisation”, in which the modern hospital, alongside its formal therapeutic function, acquired parallel, non-formal functions, has been described.